Landscape structure shapes activity levels and composition of aerial insectivorous bats at different spatial scales - Falcão, Fábio; Dodonov, Pavel; Caselli, Christini B.; dos Santos, Juliana Silveira [UNESP]; Faria, Deborah (Springer Nature, 2021)
Tropical forests are being lost and modified at an unprecedented rate, with extant biodiversity increasingly restricted to human-modified landscapes. Resulting changes in landscape structure are shaping diversity patterns, with features such as habitat amount, edge density, and matrix quality determining species persistence. We assessed the importance of landscape composition (forest amount and matrix composition) and configuration (edge density) on diversity patterns of aerial insectivorous bats in Brazilian Atlantic Forest landscapes. We sampled 40 sites in two nearby sub-regions, one contained more forest cover and shade cacao plantations while the other was less forested and dominated by pastures. Based on echolocation calls, we detected 17 sonotypes that could be attributed to at least 13 species belonging to three families. The two sub-regions comprised bat assemblages similar in species richness but different in species composition and activity levels (a surrogate for abundance). Whereas species richness was not influenced by landscape structure at the largest spatial scale of study, activity levels were shaped by changes in landscape composition and configuration, with different responses for forest and open-area foragers. Decreasing activity of forest foragers was the most evident response of bat diversity to landscape structure at different spatial scales. Given the value of this biological group for key ecosystem services such as pest control, our findings highlight the importance of considering regional landscape features for management and prediction of future scenarios of anthropization.
Keywords: Acoustic monitoring; Atlantic forest; Chiroptera; Deforestation; Landscape ecology; Neotropics